2022
DOI: 10.3390/vaccines10122168
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of SARS-CoV-2 Virus in Healthcare Workers before Circulation of the Omicron Sublineages BA.4/BA.5 in Vojvodina, Serbia

Abstract: Healthcare workers (HCWs) are a vulnerable and critical population in the ongoing response to the SARS-CoV-2 pandemic. We aimed to estimate the seroprevalence in HCWs considering all of their previous contacts with the SARS-CoV-2 virus and/or the immunity acquired through their immunization against COVID-19 before the advent of the Omicron variants BA.4/BA.5. Serum samples were collected from 28 March to 10 June 2022. We covered 25% out of all the people who worked in some of the government healthcare centers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…A study from Belgium reported seroprevalence of 15.1% before vaccination (December 2020) and an increase to 84.2% after the first vaccination among primary healthcare providers, underlining the importance of vaccination for occupational health and protection of medical personnel (21). Recently, a study from Serbia, similar to ours, reported 93.0% overall prevalence of anti-SARS-CoV-2 antibodies among HCWs before the emergence of the Omicron variant (22). In general, the seropositivity levels have increased since the first and second waves of COVID-19 and after the mass vaccination.…”
Section: Discussionsupporting
confidence: 72%
“…A study from Belgium reported seroprevalence of 15.1% before vaccination (December 2020) and an increase to 84.2% after the first vaccination among primary healthcare providers, underlining the importance of vaccination for occupational health and protection of medical personnel (21). Recently, a study from Serbia, similar to ours, reported 93.0% overall prevalence of anti-SARS-CoV-2 antibodies among HCWs before the emergence of the Omicron variant (22). In general, the seropositivity levels have increased since the first and second waves of COVID-19 and after the mass vaccination.…”
Section: Discussionsupporting
confidence: 72%
“…As the availability of Ag-RDT tests increased in Serbia, the testing algorithm was expanded so that other clinical forms became more present throughout the subsequent waves, depending on the dominant strain that was circulating. In a subsequent study that focused on health workers in state health centers (6936 participants out of 27,738 of all employees in Vojvodina), comparing the clinical manifestations they had the last time they were SARS-CoV-2 positive with their vaccination status, it was found that the highest seroprevalence of SARS-CoV-2 antibodies had asymptomatic (64.36%), mild (45.17%), severe (38.39%), and critical (45.45%) forms that received three doses of the vaccine [57].…”
Section: Discussionmentioning
confidence: 99%